Kajian buku teks pelajaran fisika SMA kelas XI semester 2 untuk memfasilitasi ketrampilan proses sains - Indri Syukra; Yenni Darvina; Desnita Desnita; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2020)
Science Process Skills (KPS) are skills used for experiments in solving problems, students can find their own facts in everyday life. Learning resources used by students one of them is a book, in addition to books learning resources can be from the teacher and the surrounding environment. Textbooks used by students in Physics learners can vary, Physics books used by students are not yet known which books facilitate science process skills. This study used a descriptive study with a qualitative approach, the study population was all physics textbooks for class XI Semester 2 high school published in Indonesia and used in all schools in West Sumatra. The sample of this study is the four books most widely used in West Sumatra schools, the most widely used books by schools are not yet known reasons for using them. This research instrument used the analyses whork sheet contain 10 science process skills indicators. This instrument has been tested for validity and preview to be valid. The Science Process Skills Indicator is broken down into 37 instruments, data collection techniques with document studies. The results obtained that the textbook textbook that facilitates the highest is the 2016 SP-YW book gets an average percentage score of 55.1% with the category of moderating enough, the KK-GR book gets an average percentage score of 51.5% with the category of facilitating enough , the MR-TS book gets an average percentage score of 50.9% with the category of moderately facilitating and the textbook with the lowest level of facilitating is the book written by the MK-ER getting an average percentage score of 40.1% with the category of less facilitating. So there is still a need to make books that have science process skills that are very facilitating.